Effect of polyamines on mineral separation of nickel-copper ores: chelation equilibria in collectorless floation with DETA - S. Kelebek (The Institute of Materials, Minerals and Mining, 1905)
DETA exhibits a highly selective depressant action on pyrrhotite without adversely affecting the collectorless flotability of pentlandite and chalcopyrite in nickel-copper ores of the Sudbury region. A simplified Eh-pH diagram has been constructed to illustrate the extended stability of elemental sulphur and to explain the collectorless flotation of pentlandite and chalcopyrite. Cu and Ni ions, which are known to exist on the surface of pyrrhotite, promote the flotation of this mineral whether a collector is present or not. Thermodynamic calculations indicate that the action of DETA involves the sequestration of Cu and Ni ions from surfaces under a wide range of redox conditions; analysis of flotation test filtrate indicates as much as a 20-fold increase in the concentration of Ni and Cu ions. It appears that DETA may enhance the self-hydrophobicity of chalcopyrite and pentlandite by exposing more of the sulphur-rich surface sites for bubble contact in flotation. There are various possible explanations for its depression of pyrrhotite